Progressive stress response of the anaerobic granular sludge to nickel nanoparticles: experimental investigations and mathematic modelling. Issue 5 (11th April 2019) - He, Chuan-Shu; Huang, Liang; Ding, Rong-Rong; Yang, Hou-Yun; Wang, Yi-Xuan; Li, Jie; Mu, Yang
Abstract : Long-term exposure to Ni-NPs induced progressive and unrecoverable inhibition of the activity of the AGS. Abstract : In recent years, efforts have been made to explore the possible impacts of nanoparticles (NPs) on the methanogenic activity of anaerobic granular sludge (AGS). However, the conclusions regarding the toxicity of NPs on the AGS were still not comprehensive enough especially for long-term exposure. The aim of the present study was to fully evaluate the long-term effects of representative Ni-NPs at various concentrations on the activity of the AGS from macroscopic and microcosmic experiments as well as simulation with a new model based on anaerobic digestion model 1 (ADM1). Both experimental and modelling results revealed that a high Ni-NP dosage induced progressive and unrecoverable inhibition of the activity of the AGS, which was first displayed by the slowing of glucose degradation in the first two cycles, followed by retardation of the acetification of propionic and butyric acids, and further the restraint of acetoclastic methanogenesis. Ni-NPs adsorbed on the surface of the AGS acted as a sustainable source of Ni 2+ for release. Cytotoxicity assays, activity tests of key enzymes, and the stress response of extracellular polymeric substances suggested that the progressive toxicity of Ni-NPs to the AGS was mainly attributed to the sustained release of Ni 2+ . High-throughput 16S rRNA gene sequencing assays and the observation of dead cells in the granule by fluorescence labeling and the CLSM technique showed that long-term exposure to Ni-NPs caused stronger inhibition of bacterial cells in the outer layer than of the aceticlastic methanogens located in the center of the AGS.